DMX AUTHORING SOFTWARE SELECTION FOR SMES’ ARCHITECTURAL AND ENTERTAINMENT LIGHTING IN CENTRAL JAKARTA - Nuryana, Muhammad Risqi; Nabila Latifa Tulaili; Resi Sujiwo Bijokangko (Engineering Journal of Implementing and Community, 2026)
The use of DMX-based lighting control systems is increasingly relevant for small and medium enterprises (SMEs) in the culinary, entertainment, and hospitality sectors in the Mangga Besar area of Central Jakarta to enhance the visual appeal of business spaces. However, the selection of DMX authoring software is often based on technician habits or vendor recommendations rather than on structured and user-oriented criteria. This community service program aims to assist SMEs in understanding and selecting DMX authoring software that fits their operational needs. The approach involved a documentation review of two commonly used applications, Euchips Designer (EuchipsX-DMX) and ColorPlay 3. Feature information and workflows were extracted from official manuals and normalized into a shared checklist covering setup/mapping, grouping, effects, timeline authoring, project/show management, and configuration and deployment support. The results were used as educational and mentoring materials for SME participants. The activity results indicate that ColorPlay 3 provides more comprehensive workflow documentation from mapping to deployment, including an effects catalog, timeline layering/stacking mechanisms, and support for data portability and playback configuration. Meanwhile, EuchipsX-DMX emphasizes timeline-based scene editing for decorative and architectural lighting with multi-zone and synchronization support, although its feature descriptions are less detailed than those in ColorPlay 3 documentation. This assistance program enabled SMEs to gain a more structured understanding of how to select and implement DMX authoring software according to their visual and operational requirements.